Design and analysis of novel low-voltage low loss RF-MEMS switch / Ma Li Ya - Ma , Li Ya (2018)

(untitled)
RF-MEMS switch is a kind of electromechanical structure that is used to short or open a RF to millimeter-wave-frequency transmission line. Compared to traditional RF switches, RF-MEMS switches possess many significant advantages, such as negligible DC power consumption, small series capacitance, resistance and insertion loss, good isolation, as well as high linearity and cut-off frequency. RF-MEMS switch can be actuated by many different mechanisms, like electrostatic, electromagnetic, thermal, and piezoelectric; among them electrostatic mechanism is the most prevalent technique in use today. However, the main challenge of the electrostatic-actuated RF-MEMS switches is their comparatively high actuation voltage (20V~80V), which makes them unsatisfied for wireless communication systems; cannot be integrated with active CMOS circuitry; and lead them to have short lifetimes. The objective of this project is to design, optimize, simulate and analyze a low-voltage low-loss electrostatic-actuated RF-MEMS capacitive switch. The research methodology follows the steps of identifying the design specification, creating the novel 3D structure, optimizing the geometric dimensions, simulating and verifying the switch’s properties, modeling the equivalent electric circuitry, and implementing it into the RF applications, namely MEMS phase shifters. The low-actuation voltage design is achieved by using novel combination of folded and spring beams which are used for supporting the switch’s big membrane; and the low-loss property is realized by employing an inductive matching circuit, namely T-match or π-match circuit. The structure of the switch is optimized by using a new developed multi-response optimization method which is based on Taguchi method and weighted principal component analysis to accomplish the aims of low-actuation voltage, robust structure, and relatively short switching time simultaneously. The final optimized RF-MEMS capacitive switch has actuation voltage of 3.06V with spring constant of 0.2378N/m, switching time of 34μs~19.5μs with bias voltage of 4V~7V, the insertion loss and isolation of -0.5487dB and -23.02dB, respectively, at frequency of 20GHz. By using T-match circuit, the insertion loss and isolation can be enhanced by 76.47% and 25.07%, respectively; and by using π-match circuit, the insertion loss can be improved by 76.53%. Two low-voltage low-loss MEMS phase shifters, namely MEMS switched-line phase shifter and DMTL phase shifter, by using proposed RF-MEMS switches are presented. For the 3-bit MEMS switched-line phase shifter, its average phase error and insertion loss is 0.5056° and -1.51dB, respectively, at 20GHz; both return loss and isolation are better than -11dB at a wideband frequency range of 18GHz to 22GHz; the design area is 6mm × 4 mm. For the 3-bit DMTL phase shifter, its average phase error and insertion loss is 6.032° and -1.526dB, respectively, at 20GHz; the return loss is better than -10.05dB for all the phase shift conditions; the design area is 12.8mm × 1.4mm.